Burnout Syndrome and Occupational Biological Exposures in Healthcare Professionals: A Systematic Review. - AMORES-LIZCANO, Ester; ROMERO-BLANCO, Cristina; GARCÍA-MARTÍNEZ, Pedro (Journal of Nursology, 2026)
Objective: To determine the relationship between burnout syndrome and psychosocial factors (poor sleep quality, stress or anxiety) and occupational biological exposures (OBE) among healthcare professionals. Methods: Systematic review conducted between January and May 2024, following the PRISMA guidelines and the PICO approach adapted to the PIO format. It was registered in PROSPERO (CRD42024528760). Searches were performed in Web of Science, PubMed, Cochrane Library, LILACS, Dialnet, and Scielo databases. The inclusion criteria comprised articles published between 2013 and 2023, written in English, Spanish, or Portuguese, that investigated the relationship between burnout syndrome and its associated psychosocial factors, as well as OBE (such as needle sticks, cuts, and splashes) in healthcare professionals. Results: Ten articles were selected: six cross-sectional, one was a prospective observational cohort study, one was an ecological study, one was a retrospective observational cohort study, and one was a combination of a quantitative cross-sectional observational study and a qualitative phenomenological study. The included studies demonstrated that occupational biological exposures (OBEs) were associated with certain components of burnout syndrome (such as low job satisfaction or emotional exhaustion), as well as with stress and poor sleep quality. Conclusion: No studies have been found that specifically measure the presence of this syndrome in workers exposed to OBE. Further research using validated instruments is needed to clarify this relationship and to inform targeted preventive strategies for healthcare professionals.